Unjuk Kerja Teknologi Akses Jamak TD-CDMA dan TD-SCDMA pada Infrastruktur Jaringan High Altitude Platform Stations - Melvi, Melvi; Nurhayati, Nurhayati; Batubara, Mona Arif Muda; Septama, Hery Dian; Ulvan, Ardian (Jurnal Teknologi Riset Terapan, 2025)
Purpose: This study evaluates the performance of TD-CDMA and TD-SCDMA access technologies for High Altitude Platform Stations (HAPS) to meet growing demands for high-speed access and larger bandwidth in telecommunications. Methodology/approach: A performance comparison was conducted between TD-CDMA and TD-SCDMA based on three key parameters: access speed, data transfer capacity, and power consumption levels. Analytical calculations were carried out to assess data capacity and transmitted power at varying distances from the HAPS. Results/findings: The analysis showed that TD-CDMA provides higher data capacity compared to TD-SCDMA. Additionally, transmitted power requirements increase with greater distances between HAPS and ground receivers, with a maximum transmitted power of 19.423 W observed at 50,000 meters. Conclutions: TD-CDMA offers better overall performance than TD-SCDMA for HAPS applications, providing higher data capacity while maintaining comparable power efficiency, making it a preferable choice for high-speed communication services. Limitations: The study is limited to theoretical calculations without real-world field testing. Factors such as environmental interference and atmospheric conditions were not included in the analysis. Contribution: This research provides insights into selecting efficient access methods for HAPS technology, highlighting TD-CDMA as the more suitable option to support high-speed, large-bandwidth telecommunication services with optimized resource utilization.